Kapčiamiestis Final Palaeolithic Site on the Bank of Baltoji Ančia River - Šatavičius, Egidijus (Archaeologia Lituana, 2021)
The article analyzes the archaeological material of Kapčiamiestis Stone Age site, which was excavated in 2006–2007. A brief overview of the site’s history and heritage conservation and management works is provided. The article analyzes the geomorphology of this area and its development in the late ice age and the Holocene, describes in detail the stratigraphy of the study site and various erosive processes that have intensively affected it. Although the findings were not found in abundance during the research, it is an object that has existed for a short time and is characterized by the homogeneity of the assemblages. Based on the information gathered during the research and the typological-technological criteria of the flint inventory, the site dates back to the end of the Final Paleolithic (10th millennium BC) and belongs to the late Swiderian cultural tradition. It is currently the oldest excavated Stone Age site on the southernmost outskirt of Užnemunė Region.
Keywords: archaeological site; lithic; Final Palaeolithic; stratigraphy; geomorphology